Underground in Japan - Ventura, Rey. (Quezon City Ateneo de Manila University Press, 2006)
Social aspects of illegal foreign workers in Japan.
First published: London, U.K. : Reynald B. Ventura, 1992.
Keywords: Illegal aliens -- Social conditions. -- Japan -- Yokohama-shi.; Filipinos -- Social conditions. -- Japan -- Yokohama-shi.; Foreign workers, Filipino -- Social conditions. -- Japan -- Yokohama-shi.